Aesthetic femininity and domestic modernity in late Victorian advice literature - Yan, Shu-chuan (College teacher), author.
1 online resource (220 pages)
Keywords: Aesthetic Femininity and Domestic Modernity in Late Victorian Advice Literature considers how the domestic interior is constituted, imag(in)ed, contested, and mediated in the public forum of advice literature. It interrogates the construction and negotiation of aesthetic femininity and domestic modernity within the larger contexts of the New Journalism, the New Art Criticism, a new girls' culture, and the emerging New Woman phenomenon in Britain.This book presents extensive new search on women-authored advice literature, including domestic advice manuals, home decoration books, and periodicals for young girls and adult women, within the discourse of household art. Part One justifies girls' presence in the cultivation of beauty and taste at home. The practice of home decoration can be appropriated as a mode of agency and subjectivity for a girl to articulate her own voice and specific positioning as she grows toward womanhood. Part Two uncovers the ways in which advice literature serves as a mediator of decorating practices to help foster the affinities between gentlewomen's domestic bodies and decorated interiors.Aimed at an interdisciplinary audience, this book adds to the growing body of scholarship on the studies of home cultures, art and interior design, nineteenth-century studies, and the social history of women.